2021
DOI: 10.3389/fvets.2021.676549
|View full text |Cite
|
Sign up to set email alerts
|

Review of Infections With Bovine Herpesvirus 1 in Slovenia

Abstract: In the 1950s, infectious bovine rhinotracheitis/infectious pustular vulvovaginitis (IBR/IPV) disease was clinically detected and documented in cattle for the first time in Slovenia. The bovine herpes virus 1 (BoHV-1) was confirmed several times from infected herds by virus isolation on cell cultures. To keep the IC virus-free, high biosecurity measures were introduced. Before entering the IC, all calves are serologically tested and quarantined. Bulls in Slovenian insemination centres (IC) have been negative fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…The incidence and prevalence of IBR are extremely variable under different geographical location and systems of rearing (Nandi et al, 2009). Prevalence of IBR is low in Slovenia 0.1% a due to ongoing eradication programmes (Hostnik et al, 2021) and in Spain region highest 99.92% (Dias et al, 2013). Pooled seroprevalence of IBR in China as per meta-analysis is 40.00% (Chen et al, 2018), prevalence in Colombia is 57.5% (Ortiz et al, 2022), Brazil, 71.30 (Abad et al, 2016 Mexico 76.32% (Posado et al, 2013) and Ethiopia, 25.6 (Tadeg et al, 2021).…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence and prevalence of IBR are extremely variable under different geographical location and systems of rearing (Nandi et al, 2009). Prevalence of IBR is low in Slovenia 0.1% a due to ongoing eradication programmes (Hostnik et al, 2021) and in Spain region highest 99.92% (Dias et al, 2013). Pooled seroprevalence of IBR in China as per meta-analysis is 40.00% (Chen et al, 2018), prevalence in Colombia is 57.5% (Ortiz et al, 2022), Brazil, 71.30 (Abad et al, 2016 Mexico 76.32% (Posado et al, 2013) and Ethiopia, 25.6 (Tadeg et al, 2021).…”
Section: Epidemiologymentioning
confidence: 99%
“…Disease was found to affect exotic and crossbred cattle in India during inception than native breeds. In Slovenia and Colombia HF cow breed (Hostnik et al, 2021) and in Nepal's Jersey breed of cattle have shown higher prevalence than other breeds (Sanjay et al, 2022). One frequent risk factor reported by many authors is herd size, where the disease was more prevalent in intensive rearing or feed lots or organised farms or farms with more than 10 animals compared to free-range Bovine Alphaherpesvirus-1 (BoHV-1) Infection in Cattle: An Overview of Epidemiology, Role of Envelope Proteins in Disease and.. animals or the unorganised sector (Rajkhowa et al, 2004).…”
Section: Epidemiologymentioning
confidence: 99%
“…It mainly affects cattle, but interspecies transmission is possible to sheep and goats. Main route of transmission is through nose-to-nose contact with nasal secretions, respiratory droplets, and semen of infected animals [ 14 ] BoHV-1 is the causative agent of acute respiratory disease, infectious bovine rhinotracheitis (IBR) and correlated with abortions as well [ 15 ]. Since it is responsible for major losses of livestock, several European countries eradicated the disease while others run eradication campaigns against BoHV-1 and especially gE (glycoprotein E)-deleted marker vaccines are being used for surveillance of the disease [ 16 , 17 ].…”
Section: Ruminant Viral Diseases and Lamp Assays For Diagnosismentioning
confidence: 99%
“…Цьому передувало широкомасштабні серологічні дослідження всього поголів'я на наявність антитіл до збудника у тварин. Зважаючи на те, що програма передбачає всі фінансові затрати по отриманню та підтримки означеного статусу покласти на власників тварин, її ефективність була на дуже низькому рівністаном на 2020 рік на території Словенії є лише одне офіційно благополучне щодо ІРТ господарство [32].…”
Section: ветеринарнаunclassified